ADSORPSI ION FOSFAT DALAM AIR TAWAR DAN AIR LAUT MENGGUNAKAN BENTONIT ALAM KOMERSIAL YANG TERJERAP PADA Fe-ALGINAT DAN Ca-ALGINAT - , SHINTA DEWI A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The phosphate ion adsorption by commercial natural bentonite entrapped in Fe-alginate and Ca-alginate has been studied. The first step of this research was characterization of commercial natural bentonite from Magelang using XRD and AAS. The particle of bentonite-Fe-alginate (B-Fe-A) and bentonite-Ca-alginate (B-Ca-A) were synthesized with a ratio of bentonite:alginate (1:1) by extrusion method. Adsorption process of phosphate ion by B-Fe-A and B-Ca-A particle was carried out in fresh water and sea water by batch system at room temperature with variation of pH, contact time, and adsorbate concentration. The results of the XRD analysis from commercial natural bentonite showed 3 dominant peaks at diffraction angle (2Î¸) with d-value of 26.65Â°(3.34Ã)